2022
DOI: 10.3390/su141912480
|View full text |Cite
|
Sign up to set email alerts
|

Social, Economic, and Financial Aspects of Modelling Sustainable Growth in the Irresponsible World during COVID-19 Pandemic

Abstract: The subject matter of this study is connected to the functions of socially responsible business, which has become an essential topic within the insurance sector during the COVID-19 pandemic. This issue has received increasing attention from scientific, business, and political communities. Our study is devoted to the social, economic, and financial dimensions of the problem concerning sustainable development, and is analysed from the perspective of the financial market, including the insurance sector, during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…After analyzing the economic indicator and identifying the significant factors influencing the long-term loans that were issued, they concluded that the banks had enough funds to support sustainable economic growth, but the commercial banks were not willing to take the credit risk due to their risk tolerance. Similarly, Przybytniowski et al [42] assume that the social, economic, and financial aspects concerning the development of Poland are related to the behavior of the financial market, which are responsible for modeling economic growth by implementing socially responsible actions both during and after the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After analyzing the economic indicator and identifying the significant factors influencing the long-term loans that were issued, they concluded that the banks had enough funds to support sustainable economic growth, but the commercial banks were not willing to take the credit risk due to their risk tolerance. Similarly, Przybytniowski et al [42] assume that the social, economic, and financial aspects concerning the development of Poland are related to the behavior of the financial market, which are responsible for modeling economic growth by implementing socially responsible actions both during and after the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%